Using a Transection Paradigm to Enhance the Repair Mechanisms of an Investigational Human Cell Therapy. (September 2022) - Chau, Monica J.; Quintero, Jorge E.; Monje, Paula V.; Voss, Stephen Randal; Welleford, Andrew S.; Gerhardt, Greg A.; van Horne, Craig G.
One promising strategy in cell therapies for Parkinson's disease (PD) is to harness a patient's own cells to provide neuroprotection in areas of the brain affected by neurodegeneration. No treatment exists to replace cells in the brain. Thus, our goal has been to support sick neurons and slow neurodegeneration by transplanting living repair tissue from the peripheral nervous system into the substantia nigra of those with PD. Our group has pioneered the transplantation of transection-activated sural nerve fascicles into the brain of human subjects with PD. Our experience in sural nerve transplantation has supported the safety and feasibility of this approach. As part of a paradigm to assess the reparative properties of human sural nerve following a transection injury, we collected nerve tissue approximately 2 weeks after sural nerve transection for immunoassays from 15 participants, and collected samples from two additional participants for single nuclei RNA sequencing. We quantified the expression of key neuroprotective and select anti-apoptotic genes along with their corresponding protein levels using immunoassays. The single nuclei data clustered into 10 distinctive groups defined on the basis of previously published cell type-specific genes. Transection-induced reparative peripheral nerve tissue showed RNA expression of neuroprotective factors and anti-apoptotic factors across multiple cell types after nerve injury induction. Key proteins of interest (BDNF, GDNF, beta-NGF, PDGFB, and VEGF) were upregulated in reparative tissue. These results provide insight on this repair tissue's utility as a neuroprotective cell therapy.